Promoting IBS Implementation Among Local Contractors in Construction Industry - Hanif, Syazwan; Mohd Roshdi, Farrah Rina (Research in Management of Technology and Business, 2024)
The term "Industrialised Building System" (IBS) is used in Malaysia to refer to a construction technique in which parts are manufactured in a controlled setting, either on or off site, before being set into an assembled into construction works. In reality, the government has already created a number of incentives to encourage local contractors to upgrade and become an IBS’s contractors. However, for this 21st century, the total number of contractors who applied the IBS system is still fairly small, despite the government’s efforts to promote its use. From this perspective, the goal of this research to identify a several strategies for promoting IBS implementation among local contractors in upgrading their expertise in IBS for construction industry. Additionally, a quantitative approach and a questionnaire survey have been utilised as the data collection instruments to accomplish these goals. Purposive non-probability sampling was utilised as the sampling technique, the sample frame and questionnaire were given to 310 G7 contractors involved with building construction in Kuala Lumpur. Subsequently, data analysis software called Statistical Package for Social Science (SPSS) was utilised to examine the results. Due to an extensive familiarity with and understanding of the IBS system, the majority of contractors are motivated to adopt it. The highest strategies are 68.3% external push from government, 65.6% build more IBS manufacturers, and 67.8% more training course regarding IBS programmes. Finally, since every strategy received a strongly agree score, it can be said that most respondents are agree with it.